Local Government Strategy in Managing the Balang-Balang Traditional Market of Gowa Regency - Arman (Newinera Publisher, 2020)
This study discusses the Regional Government Strategy in the Management of Balang-Balang Traditional Market in Gowa Regency and knows the things that influence the strategies of the local government in Balang-Balang Traditional Market Management in Gowa Regency. The research approach used is descriptive qualitative. Data obtained from interviews and observations were then analyzed by looking at regional government program strategies in Balang-Balang market management along with the inhibiting factors found in this study. The activities in data analysis in this study are data reduction, data presentation, and drawing conclusions. The results of the research show that there are programs implemented by the local government, one of them is business development and trade facilities that highlight market planning and revitalization efforts, the Gowa Regency government's strategy of prioritizing the improvement of public market facilities in order to operate the process of repairing facilities prioritizing parking facilities causing congestion problems. in the area of ​​the road near the market but the achievement of the objective for price stability in traditional markets is well controlled. In the aspects of leadership, motivation and communication system, there is a process of interaction between the market manager and the Trade Industry Office to check if there is a procedural mismatch.